Relationship between diet, sociodemographic factors, and body composition in students from UNEMI and ESPOCH - Suaárez-González, Katherine Denisse; Solis-Manzano, Angélica María; Padilla-Samaniego, María Victoria; Sandoval-Tamayo, Verónica Patricia; Morales-Caluña, Edgar Rolando (Frontiers in Public Health, 2025)
IntroductionThe nutritional habits and sociodemographic background of university students are critical factors influencing their body composition and long-term health. This study aimed to analyze the relationship between diet quality, sociodemographic factors, and body structure among students from the State University of Milagro (UNEMI) and the Higher Polytechnic School of Chimborazo (ESPOCH) in Ecuador.MethodsA cross-sectional design was applied to a sample of 404 students selected through stratified random sampling. Data were collected via structured interviews, 24-hour dietary recall, and food frequency questionnaires, along with anthropometric and clinical evaluations. Statistical analyses included one-way ANOVA and Kruskal–Wallis tests to assess associations, stratified by sex.ResultsOnly 2% of students maintained a nutrient-rich diet, while over 78% had nutrient-poor dietary patterns. Among women, higher fat intake was significantly associated with elevated triglyceride levels (p = 0.010), and nutrient-rich diets correlated with lower systolic blood pressure (p = 0.000). Among men, high-fat diets were linked to increased systolic and diastolic blood pressure (p = 0.007 and p = 0.004, respectively). Sociodemographic analysis revealed that men born in the Highland region had significantly higher body fat percentage and hip circumference than those from the Coastal region. A trend in muscle mass percentage according to paternal origin was also observed.ConclusionThe findings highlight the importance of addressing both dietary behaviors and sociodemographic contexts in university health promotion. Nutritional education tailored to regional and cultural backgrounds, alongside strategies to promote physical activity, could support healthier body composition and reduce cardiovascular risks in young adults.